2012
DOI: 10.1038/nature10842
|View full text |Cite
|
Sign up to set email alerts
|

Insights into hominid evolution from the gorilla genome sequence

Abstract: Summary Gorillas are humans’ closest living relatives after chimpanzees, and are of comparable importance for the study of human origins and evolution. Here we present the assembly and analysis of a genome sequence for the western lowland gorilla, and compare the whole genomes of all extant great ape genera. We propose a synthesis of genetic and fossil evidence consistent with placing the human-chimpanzee and human-chimpanzee-gorilla speciation events at approximately 6 and 10 million years ago (Mya). In 30% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
617
8
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 692 publications
(682 citation statements)
references
References 47 publications
47
617
8
4
Order By: Relevance
“…Furthermore, the heterozygosity rate was the lowest in the Comoro individual (Supplemental Tables 20,21). The lower heterozygosity rates in coelacanth individuals, as compared with those in human (0.069%) (Wang et al 2008) and gorilla (0.076 to 0.189%) (Scally et al 2012), are also consistent with the idea of a lower nucleotide substitution rate in coelacanths.…”
Section: Heterozygosity Ratesupporting
confidence: 72%
“…Furthermore, the heterozygosity rate was the lowest in the Comoro individual (Supplemental Tables 20,21). The lower heterozygosity rates in coelacanth individuals, as compared with those in human (0.069%) (Wang et al 2008) and gorilla (0.076 to 0.189%) (Scally et al 2012), are also consistent with the idea of a lower nucleotide substitution rate in coelacanths.…”
Section: Heterozygosity Ratesupporting
confidence: 72%
“…Using these reads, we identified 16.5 million putative variants among the 4 species. The rates at which heterozygous variants occurred indicated that the level of genetic diversity among the species of snub-nosed monkeys was much lower than for all other reported nonhuman primates (0.02-0.07% in comparison to 0.08-0.24%) 26,27 , with R. brelichi showing the highest value (0.07%), which approaches the human value (0.066%). The proportions of autosomal regions of homozygosity (ROHs) also supported the differences in heterozygous SNPs among snub-nosed monkeys ( Fig.…”
Section: Genomic Variation and Demographic Historymentioning
confidence: 65%
“…The short branches of these lineages in the tree also imply that incomplete lineage sorting (ILS; cases where the gene tree was different from the species tree) and/or introgression have occurred within this clade. Using the coalescent hidden Markov model (CoalHMM) 32,33 , we quantified the amount of ILS as ~5.8% of the genomes in the snub-nosed monkeys on the basis of all SNPs (regions where R. roxellana and R. brelichi were more closely related to R. bieti than to R. strykeri), a ratio less than that (~30%) found in the genomes of great apes (human, chimpanzee and gorilla) 27 . CoalHMM was also employed to date the speciation events within this lineage, and the results supported a relatively recent isolation of snub-nosed monkeys: 0.15 ± 0.10 million years ago for the Himalayan species and 0.62 ± 0.17 million years ago for the northern species.…”
Section: Genomic Variation and Demographic Historymentioning
confidence: 99%
“…These results provide insights into how dietary factors could have influenced the acquisition of particular gut microbiomes and diverse gut metabolic capabilities in two different, non-sympatric gorilla species. By combining functional, dietary and longitudinal data, we suggest that upon splitting from a common ancestor around 1.75 million years ago (Scally et al, 2012), western lowland gorillas evolved a gut microbiome with increased capacity to metabolize lipids, sterols and more digestible carbohydrate sources in a nutritionally diverse dietary niche. In contrast, it seems that mountain gorillas, constrained by low nutritional diversity, evolved distinct diet-microbe co-metabolic traits, with more active plant cell wall-processing roles.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the genus Gorilla, our closest evolutionary relatives after Pan (chimpanzees and bonobos), experienced particular ecological challenges over the course of evolution that resulted in their diversification into two species, around 1.75 million years ago (Doran and McNeilage, 1998;Scally et al, 2012). Important differences within each species' habitat in relation to geographical range, food availability and climate make them interesting models to test hypotheses of how primate gut microbiomes are shaped by host-phylogenetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%